Comparison of Ferrous Sulphate with Iron Polymaltose in Treating Iron Deficiency Anaemia in Children - Tariq Mahmood, Tariq Masood Khan,Naila Khizar, Tariq Mahmood, Tariq Masood Khan,Naila Khizar (Journal of Rawalpindi Medical College, 2017)
Background: To compare the efficacy of ferrous sulphate vs Iron polymaltose complex for the treatment of iron deficiency anaemia in children. Methods: In this randomized control trial , 170 children having iron deficiency anaemia with hemoglobin< 10g/dl and serum ferritin levels below 6ng/ml were selected . Patients were randomly allocated into Group A, given Syrup ferrous sulphate in a dose of 6mg/kg/day of elemental iron once daily for 4 weeks and Group B, given syrup iron polymaltose complex in a dose of 6mg/kg/day of elemental iron once daily orally for 4 weeks. Results: - The average age was 24.86±17.85 months. The efficacy was significantly high in ferrous sulphate as compare to Iron polymaltose complex for the treatment of iron deficiency anaemia (p=0.009). Conclusion: Ferrous sulphate has advantage over iron polymaltose complex in treatment of iron deficiency anaemia where rise in haemoglobin was considered